Leptomeningeal carcinomatosis and breast cancer: a systematic review of current evidence on diagnosis, treatment and prognosis - Ludovica Mollica; Claudia Leli; Silvia Puglisi; Silvia Sardi; Federico Sottotetti (BioExcel Publishing Ltd, 2021)
Leptomeningeal carcinomatosis (LC) is a rare but challenging manifestation of advanced breast cancer with a severe impact on morbidity and mortality. We performed a systematic review of the evidence published over the last two decades, focusing on recent advances in the diagnostic and therapeutic options of LC. Lobular histology and a triple-negative intrinsic subtype are well-known risk factors for LC. Clinical manifestations are diverse and often aspecific. There is no gold standard for LC diagnosis: MRI and cerebrospinal fluid cytology are the most frequently used modalities despite the low accuracy. Current standard of care involves a multimodal strategy including systemic and intrathecal chemotherapy in combination with brain radiotherapy. Intrathecal chemotherapy has been widely used through the years despite the lack of data from randomized controlled trials and conflicting evidence on patient outcomes. No specific chemotherapeutic agent has shown superiority over others for both intrathecal and systemic treatment. Although endocrine therapy was heuristically considered unable to exert significant control on central nervous system metastatic disease, retrospective data suggest a favourable toxicity profile and even a possible positive impact on survival. In recent years, encouraging data on the use of targeted agents has emerged but further research in this field is required. Palliative treatment in the form of whole brain or stereotactic radiotherapy is associated with improvement in clinical manifestations and quality of life, with no proven impact on survival. The most investigated prognostic factors include performance status, non-triple-negative disease and multimodal treatment. Validation of prognostic scores is necessary to aid clinicians in the identification of patient subgroups that are most likely to benefit from an intensive therapeutic approach.